An empirical study on local visitors' behaviour and perceptions towards influencing factors and preferences of types of attractions, the themes and sources of information in decision making of theme park in Malaysia - Hasan, Mohmed Razip (2001)
Theme park has been identified as one of the new tourist products in Malaysia that has a great potential in attracting locals to spend their holidays in the country and also to foreign tourists, especially hose from ASEAN, South Asia and the Middle East markets to take vacation here. Many new theme parks have been developed and the existing ones are being upgraded to suit the demand and tastes of visitors. The main objective of this study is to identify and analyze travel behaviour and perceptions of local visitors towards theme park in Malaysia. The key research issues are to determine the important influencing factors, preferred types of attractions, the themes and source of information in making decision to visit a theme park. This study consists of a survey of 300 randomly selected respondents living in Klang Valley. Self-administered questionnaires are circulated and only 282 responded, of which 86.2% indicate that they have visited theme parks in Malaysia in the last three years. All data collected are processed and analyzed using SPSS Version 10.0 program. The analyses include the frequency, descriptive, reliability and hypothesis testing. The results show that cleanliness and safety are the most influential factors, fun rides as the important type of attraction and water world theme is the highly preferred. Mean while past experience and words of mouth are the most important sources of information. In terms of popularity, Sunway Lagoon is the top rated theme park and followed by Genting Indoor and Outdoor Theme Park, The Mines Wonderland, A'Famosa Water World and Wet World Shah Alam. The overall experience of most visitors is satisfactory despite some complaints about expensive food and souvenir items as well as admission fee. Thus, to further enhance the image of local theme parks in the eyes and minds of local visitors and also to improve their service quality, tourism promoters and theme park operators are recommended to incorporate the findings of this study in their strategic marketing plans and service offerings.